2020
DOI: 10.1055/s-0040-1709116
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Auditory Stream Segregation in Musicians and Nonmusicians

Abstract: Introduction One of the major cues that help in auditory stream segregation is spectral profiling. Musicians are trained to perceive a fine structural variation in the acoustic stimuli and have enhanced temporal perception and speech perception in noise. Objective To analyze the differences in spectral profile thresholds in musicians and nonmusicians. Methods The spectral profile analysis threshold was compared between 2 groups (musicians and nonmusicians) in the age range between 15 and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…In support to the literature on binaural processing ( Johnson et al., 2021 ; Luiz et al., 2021 ; Parbery-Clark et al., 2013 ), the findings of the current study also showed an binaural processing advantage in both the musical groups (vocalists and instrumentalists), who outperformed their non-musician conterparts ( Fig. 2 a and b).…”
Section: Discussionsupporting
confidence: 91%
“…In support to the literature on binaural processing ( Johnson et al., 2021 ; Luiz et al., 2021 ; Parbery-Clark et al., 2013 ), the findings of the current study also showed an binaural processing advantage in both the musical groups (vocalists and instrumentalists), who outperformed their non-musician conterparts ( Fig. 2 a and b).…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have focused on the processes involved to split a sequence into two or several streams (van Noorden, 1975), often addressing the question of auditory perceptual organization expressed along the frequency dimension -albeit necessarily involving time. Results showed that musicians develop an enhanced ability to process distinct streams out of a sound mixture, consistent with their daily experience in extracting melodies out of an orchestral background, which is one of the most complex function of the auditory system (Zendel and Alain, 2009;Johnson et al, 2021). The interleaved melody recognition task (IMRT), which involves a probe melody compared with a mixed sequence composed of a target melody, identical to the probe melody, or a modified version, interleaved with distractor tones, is an objective and indirect measure of auditory streaming proposed by Dowling (1973).…”
Section: Introductionsupporting
confidence: 57%
“…Several studies have showed that more familiar music facilitates concurrent linguistic tasks by increasing arousal (Weiss et al, 2016) and generating expectancies (Bendixen, 2014; Russo & Pichora-Fuller, 2008). Musical ability is associated not only with speech-in-noise processing advantages (Hennessy et al, 2022; Mankel & Bidelman, 2018; Yoo & Bidelman, 2019), but also parsing complex auditory scenes (Johnson et al, 2021; Zendel & Alain, 2009). Indeed, there is some evidence that trained musicians also more successfully deploy attention in auditory and even non-auditory perceptual tasks (Bialystok & DePape, 2009; Román-Caballero et al, 2020; Yoo & Bidelman, 2019), including those related to cocktail party listening (Bidelman & Yoo, 2020).…”
Section: Discussionmentioning
confidence: 99%